Immersion periods in four neotropical turtles - Morera Brenes, Bernal; Mónge Nájera, Julián Antonio 1960- (San José, Costa Rica : EUNED, 2011)
Semi-aquatic turtles often dive to escape from terrestrial predators, but to our knowledge, the time that Costa Rican species can stay under water is unknown. To obtain preliminary measurements of this ecologically significant parameter, we tested several individuals in an aquarium with water at 25°C in Sabanilla, San José, Costa Rica. We placed the turtles in the water and moved a hand on the surface whenever they attempted to swim upwards, but otherwise allowed them to resurface. They were all adult females except for Kinosternon scorpioides (3 males,1 female). The times they stayed under water were: K. scorpioides 60-3656s (15 repetitions); Kinosternon leucostomum 82-84s (6 repetitions); Rhinoclemmys pulcherrima 413-435s (2 repetitions) and R. funerea 525 seconds (one test).The maximum time was of about one hour, recorded for a female K. scorpioides. Standora et al. (1984) found that in nature, submersion times for the marine Dermo-chelyx coriacea averaged 480 seconds, similar to the times we recorded for Rhinoclemmys.
Colección Especial Editorial Universidad Estatal a Distancia-Euned
Keywords: UNIVERSIDAD ESTATAL A DISTANCIA -- Vicerrectoría de Investigación -- COSTA RICA; UNIVERSIDAD NACIONAL DE HEREDIA -- Escuela de Ciencias Biológicas -- COSTA RICA; CONSERVACIÓN DE LA VIDA SILVESTRE; CONSERVACIÓN DE ANIMALES DE CAZA; TORTUGAS; CONSERVACIÓN DE LOS RECURSOS MARINOS; DIVERSIDAD BIOLÓGICA; RESERVAS Y PARQUE MARINOS; PUBLICACIONES PERIÓDICAS